The Genetic Relationship between Three Trichoderma Species and Inhibitory Effects of T. Harzianum (Rifai) On Ganoderma Boninense - Siddiquee, Md. Shafiquzzaman (2007)
Trichoderma is a genus of soil-borne fungus with abundant reports on its success as biological control agents of a variety of plant pathogens. Antagonistic assessment by dual culture technique showed that 18 out of 48 selected T. harzianum isolates successfully inhibited the mycelial growth of the pathogen Ganoderma boninense (isolate: PER71) at 47.86 to 72.06% with the strongest inhibitor exhibited by strain FA30. Eight samples produced effective volatile antifungal compounds which suppressed the growth of PER71 at 24.528 to 58.70 % over 6 days. When the 10 samples were assayed for the production of non-volatile antifungal compounds, whereby showed the inhibitory effects of 18.35 to 40.16% over 6 days. Strain FA30 was the best inhibitor isolate not only by dual culture inhibition technique, but was also the best producer of volatile and non-voltile inhibitor compounds, at 58.70 and 40.16% respectively. The identifications of species of Trichoderma worldwide are currently deduced from micro-morphological descriptions which is tedious and prone to error. This study undertook a molecular approach, using isozyme electrophoresis, random amplified microsatellite (RAMS) analysis and gene sequence of the internal transcribed spacer-1 (ITS 1) region of the ribosomal DNA of selected Trichoderma isolates. Electrophoretic variation of nine isozyme systems of 47 isolates from 3 species of Trichoderma namely, T. harzianum, T. aureoviride and T. longibrachiatum were studied. The UPGMA cluster analysis of the isozyme data showed the putatively identified T. harzianum to be distinctly separated from the outgroup sample of T. longibrachiatum, whereas T. aureoviride showed a closer genetic relationship to the T. harzianum populations. No distinct conclusion could be drawn from the dendrogram as the level of separation between T. harzianum and T. aureoviride and may not necessarily indicate a difference at the species level. A second molecular approach used was to extract DNA and characterise the sample for their Random Amplified Microsatelite DNA (RAMS) profile. The RAMS generated dendrogram showed that besides the distinct T. longibrachiatum, 2 other lineages were evident by UPGMA analysis. Again the level of taxonomic difference could not be determined. However, no clear separation was obtained by the dendrogram generated by the neighbor-joining (NJ). The third approach was to putatively sequence the samples using the internal transcribed spacer 1 (ITS 1) region of the rDNA. The nucleotide sequences were multiple aligned and compared against the ex-type strains sequences from the NCBI and TrichoBLAST Genbank database. Results showed that 25 out of the 26 putatively identified T. harzianum were in agreement with the genome of the T. harzianum ex-type strain while the single exception belonged to T. virens instead. The 9 putative T. aureoviride were misidentifications where 7 were T. harzianum and 2 were T. virens based on the Genbank database. The single strain of T. longibrachiatum (IMI: 375055) was in agreement with the ex-type strain. This study showed that conventional identification of T. harzianum, despite being done under the best possible care and condition, can still lead to incorrect identifications. Molecular studies by isozyme analysis did not give confident level of separation at the species level. The dendrogram based on UPGMA from RAMS analysis supported the ITS 1 gene sequence analysis but it could not confirm the specific species level. The ITS 1 region study showed that the gene sequences of Trichoderma samples were the most accurate technique for identification, with a bootstrap stability at 100% and a homology of 98-100%.